The effects of fluid resuscitation on the hemodynamic parameters of experimental induced endotoxemia in the neonatal calves - Enes Akyüz; Alparslan Coşkun; İsmail Şen (Eurasian Journal of Veterinary Sciences)
Aim: Endototoxin is known to be an important mediator of gram negative bacterial sepsis. Endotoxemia is associated with high mortality rates in neonatal calves. Therefore, a safe and effective treatment for endotoxemia in calves is needed in order to address this common and potentially fatal condition. The primary aim of the study is to determine the effects of NaCl on the clinic, hematologic and hemodynamic parameters of calves. Materials and Methods: Twelve healthy calves, aged between 5 to 15 days included into the study. Calves which included into the study randomly divided two groups as lypopplisaccharide (LPS) and Control groups: Group I(LPS): 0.9% NaCl (IV) was given to calves at 1th hour following of LPS administration (1 μg/kg, IV, 50 mL 0.9% NaCl/30 min). Group II (Control): Only 0.9% NaCl (IV, 50 mL/30 min) was given to calves. Blood samples were taken from vena Jugularis before LPS infusion at 0 h (base line) and after LPS infusion at 1, 2, 4, 6, 8, 12, 18, 24, 36, 48, 72, and 96 hours. Results: Following the LPS administration, increase in lactate levels and heart rate as well as decrease in systolic and mean arterial pressures were indicated the failure in circulatory system. However, administration of 0.9% NaCl was improved this parameters near the base line at within 8 and 12 hours of study period. Conclusion: It may be concluded that the use of 0.9% NaCl in treatment of the endotoxemia would be useful in neonatal calves.